2016
DOI: 10.1002/adom.201600155
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Precision of 3D Polymerization via Polarization Control

Abstract: COMMUNICATIONand as self-organized nanopatterns induced on a surface, [ 30 ] are among other polarization-related phenomena demonstrated recently.The infl uence of beam polarization orientation on laser processing has been thoroughly studied in the cases of conductive and dielectric solid targets. [ 31,32 ] There are known effects of polarization on the scalar parameters of laser-matter interaction, such as absorption coeffi cient and ionization rate. [33][34][35][36] It is also known that heat conduction fl u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 58 publications
(99 reference statements)
1
48
0
Order By: Relevance
“…The path of the laser was directed through the epoxy encapsulate for this process. We found that the direction of writing in relation to beam polarization had no significant effect on conductivity, although recent work has indicated polarization can play a role in photothermal processes and further work is required to confirm this [46]. From the surface wires, vias were fabricated through the PI film to form external contacts.…”
Section: Resultsmentioning
confidence: 84%
“…The path of the laser was directed through the epoxy encapsulate for this process. We found that the direction of writing in relation to beam polarization had no significant effect on conductivity, although recent work has indicated polarization can play a role in photothermal processes and further work is required to confirm this [46]. From the surface wires, vias were fabricated through the PI film to form external contacts.…”
Section: Resultsmentioning
confidence: 84%
“…Polarization of the laser beam E was perpendicular (and parallel) to the scanning direction, which corresponded to reduced (enhanced) electronic thermal conductivity. 19 However, at the employed low-NA focusing and repetition rate <0.2 MHz, anisotropy in heat flow was negligible and there was no measurable difference in the width of silk patterned silk lines.…”
Section: Samples and Proceduresmentioning
confidence: 95%
“…The asymmetry of the heat-affected zone can explain the observed variations in the nanograting period, width and tilt, as discussed in details in the following sections. It should be noted that the manifestation of such enhanced heat diffusion along the E-field in 3D laser printing has also been observed in two-photon polymerization processes5.…”
Section: Resultsmentioning
confidence: 80%